Designing knowledge management interventions in agricultural research for development: methodology, experiences, and lessons learned - Staiger Rivas, Simone; Álvarez, S.; Arana, José Antonio; Howland, Fanny C.; Cunha, Flavia; Valencia, B.; Muñoz, L.A.; Feijoo, K (2014)
The International Center for Tropical Agriculture (CIAT, its Spanish acronym) developed a methodology by which its research programs and projects can design knowledge management (KM) plans according to their impact pathways. For 2 years, the KM group applied concepts of Theory of Change to four pilot projects of the Center’s Decision and Policy Analysis Research Area to identify, design, and implement appropriate KM interventions and derive lessons.